Effectiveness of Mangosteen Peel Pressed Water (Garcinia mangostana L.) as an Organic Agent for Examination of Feces Confirmed Helminthiasis - Rohmaniar, Delianti; Aisyah, Riandini; Bestari, Rochmadina Suci; Risanti, Erika Diana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aimed to compare the effectiveness of mangosteen peel pressed water without the addition of other ingredients with mangosteen peel pressed water (Garcinia mangostana L.) which has been added with citric acid as an organic agent in fecal examinations confirmed helminthiasis. This study is very relevant considering the global health problem of worms, which is often exacerbated by poor sanitation and traditional diagnostic methods that can pose health risks. Methodology: An experimental design was conducted with a post-test only group design. The study involved nine treatments and three repetitions, utilizing fecal specimens that tested positive for helminthiasis. The mangosteen peel pressed water was prepared in varying concentrations (10%, 20%, 30%, and 40%), both with and without citric acid. The effectiveness of the dye was assessed through various parameters, including staining quality and visualization of parasitic structures. Results: The analysis indicated that all concentrations of mangosteen peel pressed water demonstrated consistent effectiveness in staining. Statistical evaluation using the Kruskal Wallis test revealed no significant differences among the treatments, with p-values for effectiveness (0.645), visualization of parasitic structures (0.364), and quality of staining (0.463). This suggests that the different concentrations and conditions did not significantly impact the outcomes, confirming the reliability of mangosteen peel pressed water staining agent for feces examination. Applications: The findings support the use of mangosteen peel pressed water as a safe and effective alternative dye for detecting helminthiasis, leveraging its anthocyanin content. This research contributes to developing more environmentally friendly diagnostic methods, reducing reliance on potentially harmful chemicals used in traditional staining processes. By enhancing diagnostic accuracy, this study has the potential to improve community health outcomes in areas affected by helminthiasis, particularly in regions with limited access to safe diagnostic tools.